THE VALIDITY TEST OF DEPRESSION SCREENING INSTRUMENT IN ADOLESCENCES - Anak Agung Wantini (Universitas Airlangga, 2019)
Background: The total estimates of people living with depression have increased by 2% from 2005 to 2015. Depression cases can be managed by screening for depression that has good validity. Purpose: This study aims to assess the validity of a depression screening instrument and provide suggestions for the development of depression screening programs. Methods: This study used an analytic observational study and the design study was a cross- sectional approach. The data were analyzed and presented in a descriptive manner. The sample size was 57 adolescents in senior high school. This screening used The Center for Epidemiological Studies Depression Scale (CES-D) questionnaire for instrument screening and Zung Self Depression Scale (SDS) questionnaire for gold standard. The screening was performed with interviews according to questionnaire guideline. The final screening evaluation was conducted by a psychologist. Results: The interview conducted using the screening instrument guideline gathered 47 respondents (82.46%) who have the tendency of depression and the gold standard showed 1 respondent (1.75%) who has the tendency of depression, while the prevalence based on the gold standard was 1.75%. The results of the validity test showed sensitivity 1 (100%), specifications 0.17 (17.85%), negative predictions 1 (100%), and positive predictions of 0.02 (2.12%). Conclusion: The validity result of screening instrument is not good enough. The weakness of this study is the results cannot be applied widely